Energy harvesting from and vibration response of different diameter cylinders. (15th November 2020) - Chen, Zhenlin; Alam, Md. Mahbub; Qin, Bin; Zhou, Yu
Highlights: Energy harvesting from flow-induced vibrations (FIV) is systematically investigated. Combined VIV and galloping vibration appear for small ξ and separated VIV and galloping for high ξ . With ξ increasing, the bandwidth of VIV contracts and the onset speed of galloping drops. The galloping offers harnessed power P three times larger than the VIV. Abstract: Energy harvesting from flow-induced vibrations (FIV) of an elastically-supported cylinder (diameter D ) immersed in the wake of another cylinder with diameter d is systematically investigated. The diameter ratio of the two cylinders is d/D  = 0.4. The incoming flow velocity considered is U∞ = 1.54–9.0 m/s, corresponding to Reynolds number Re  = 3.3 × 10 3 to 1.95 × 10 4 . A controllable magnetic damping system that can add harnessing damping ratio ξ is used to convert wind to electrical energy. The ξ is varied from 0.00091 to 0.00249. The cylinder spacing ratio L/d is varied from 1.0 to 4.0, where L is the distance from the upstream cylinder center to the forward stagnation point of the downstream cylinder. The vibration responses comprise combined vortex-induced vibration (VIV) and galloping vibration for small ξ and separated VIV and galloping for high ξ . The galloping offers harnessed power P three times larger than the VIV. The maximum efficiency η is 11.2–14.6% in the VIV regime but is only 1–2% and almost independent of reduced velocity Ur and ξ in the galloping regime.